Selection rules for all-optical magnetic recording in iron garnet - A. Stupakiewicz (Nature Portfolio, 2019)
The authors computationally and experimentally derive the selection rules on polarization, wavelengths, and magnetic damping for non-dissipative аll-optical magnetic recording with femtosecond laser pulses in Co-doped garnet film. The suggested approach is based on a multiple resonant pumping of localized d-electron transitions.